Green electricity generation from biogas of cattle manure: An assessment of potential and feasibility in Pakistan - Arshad, Muhammad; Ansari, Abdur Rahman; Qadir, Rahman; Tahir, Mudassir Hussain; Nadeem, Ans; Mehmood, Tahir; Alhumade, Hesham; Khan, Nasrullah (Frontiers in Energy Research, 2022)
In different countries, organic or municipal solid wastes such as cattle and buffalo manure have become a serious political and environmental issue due to organic waste incineration and garbage disposal. To overcome this problem, biogas production from manure is a green treatment that contributes to the availability of sustainable energy as well as assists in reducing the global warming. The current study was conducted on the generation of green electricity from cattle and buffalo manure in Pakistan. In 2021, Pakistan has generated 102.742-Terawatt hour (TWh) electricity collectively; biogas share in total production was only 0.98% which is about 1 TWh. Unfortunately, most of the electricity was generated from non-renewable energy sources. One large animal produces 9-10 kg manure per day. For the collection of manure a system can be developed , 30 % of total manure dropped every day by cattle and buffalo can be collected. Such type of system is already working for the collection of poultry manure. Pakistan has been blessed with almost 42.4 million buffaloes and 51.5 million cattle. Annual collection of manure from cattle and buffalo at the rate of 30 % will be 92.53 million tons . From this manure, about 4.63 billion m3 biogas can be produced and 70 % is collectable which will be 3.24 billion m3. Thus, Pakistan has the potential of generating 19.79-(TWh) electricity per from cattle and buffalo manure. Biogas has the potential to generate over 20 % of Pakistan's total electricity. At the farm level, 100 cattle ranches with 60 percent collected manure can create roughly 57 percent of their total consumed electricity. Slurry, a result of anaerobic digestion, can be used as a bio fertilizer in fields. It is possible to use cattle manure to make biogas, which is "made by fermentation of organic waste in the absence of oxygen." It aids in the reduction of fossil fuel dependency, solid waste management, and air pollution control by lowering greenhouse gas emissions. Biogas contributes to the three pillars of sustainable development: economic, environmental, and social development. Biogas contributes significantly to the SDGs and other aspects of sustainable development (SDDs).